Perancangan Media Pembelajaran Informatika Menggunakan Scratch Kelas X di SMAN 3 Padang Panjang - Innesha Putri; Supriadi Supriadi; Supratman Zakir; Liza Efriyanti (Lembaga Yasin AlSys, 2026)
Although the integration of technology in education has developed rapidly, the use of technology as a learning medium for Grade X Informatics at SMAN 3 Padang Panjang still needs to be optimized because the learning process remains dominated by conventional methods that affect students’ low motivation. This study aimed to produce learning media using Scratch for the Grade X Informatics subject that met the criteria of validity, practicality, and effectiveness. This study employed a Research and Development (R&D) method with the 4D development model (Define, Design, Develop, Disseminate). The research subjects involved 35 Grade X students of SMAN 3 Padang Panjang in the 2024/2025 academic year. Data were collected through observation, interviews, and questionnaires, then analyzed using Aiken’s V formula for validity, Moment Kappa for practicality, and N-Gain Score for effectiveness. The results showed that the Scratch-based learning media was declared highly feasible, with an average validity score of 0.96 in the valid criterion. The product practicality level obtained a score of 0.92 in the very high category based on educator assessment, while the effectiveness test showed a G-Score of 0.84, which was included in the high effectiveness category. These findings indicate that Scratch-based learning media contributes to transforming abstract material into interactive visuals that support students’ active engagement. The conclusion of this study affirms that the use of game-based learning elements in Scratch is effective as an alternative digital teaching material in Grade X Informatics learning. The practical implication of this study is the availability of digital learning media that can be operated offline to support the optimization of school laboratory facilities and the implementation of Kurikulum Merdeka.